Confronting the Environmental Fallout due to Polyurethane Waste and Microplastic Pollution: Mini-review - Jonidi Jafari, Ahmad; Tangestani, Mahbubeh; Zarezadeh, Elnaz (Shahroud Journal of Medical Sciences, 2025)
Background: Polyurethane plays a crucial role in waste management due to its wide range of applications and unique properties. Polyurethane waste is produced in large quantities, creating challenges for proper disposal. Inadequate disposal practices contribute to the release of polyurethane-derived microplastics through production, degradation, and wear processes, posing risks to soil, water, and air quality, as well as to ecological and human health. Despite increasing research, the environmental consequences of polyurethane waste and microplastic formation remain insufficiently synthesized, and existing management strategies are fragmented. Methods: This mini-review systematically examines the environmental impacts of polyurethane waste and microplastic pollution by analyzing studies published up to January 2024 in international and Iranian databases. Emphasis is placed on identifying current management approaches, their effectiveness, and gaps in knowledge. Results: Findings indicate that polyurethane wastes are highly persistent, amplifying their ecological footprint over time, and that recycling and recovery technologies remain limited in scope and efficiency. Few studies provide comprehensive evaluations of polyurethane-derived microplastic concentrations or their long-term hazards. The synthesis highlights the importance of innovative recycling methods, preventive measures, and public awareness initiatives as key strategies to mitigate impacts. Conclusion: The recognition of the importance of polyurethane in waste management shows the need for concerted efforts to effectively address its environmental consequences. By clarifying existing knowledge gaps and future research priorities, this study provides a focused perspective for advancing sustainable alternatives and reducing the environmental burden of polyurethane.